Rare association of obstructed supracardiac total anomalous pulmonary venous connection with coarctation of aorta: case report - Mane, Shrikant (International Journal of Contemporary Pediatrics, 2022)
Coexistence of TAPVC (total anomalous pulmonary venous connection) and coarctation of aorta rarely occurs. Newborn weighing 2.4 kg admitted in Sangli civil hospital NICU with respiratory distress with cyanosis. Chest X-ray of baby was suggestive of ground glass appearance of bilateral lung fields and cardiomegaly. SpO2 of baby was fluctuating between 85 to 90% on nasal CPAP. 2D echo showed baby was having obstructed supracardiac TAPVC with severe discrete post-ductal coarctation of aorta. There was stretched PFO shunting R-L and small PDA shunting R-L. Baby was planned for emergency surgery but couldn’t make it to operation theatre and succumbed within 30 hours of life. Till now there are very few case reports of TAPVC with coarctation but no case of obstructed supracardiac TAPVC with coarctation has been reported.